Solitary wave characteristics on the fine structure of the mesospheric sporadic sodium layer - Qiu, Shican; Shi, Mengxi; Yousof, Hamad; Soon, Willie; Jia, Mingjiao; Xue, Xianghui; Li, Tao; Ju, Peng; Dou, Xiankang (Frontiers in Astronomy and Space Sciences, 2023)
The so-called sporadic sodium layers (SSL or NaS) is proposed to be strongly related to wave fluctuations. Solitary wave is a particular solution of partial differential equation whose energy travels as a localized wave packet. A soliton, on the other hand, is a special type of solitary wave that exhibits a particle-like behavior with a strong stable form. For the first time, the solitary wave theory has been used in this research to study the fine structure of SSL/NaS. We performed soliton fitting processes on the observed data from the Andes Lidar Observatory, and found out that 24/27 NaS events had exhibited similar features/characteristics to a soliton. Time series of the net anomaly of the NaS revealed the same variation process to the solution of a generalized five-order KdV equation. Our results, therefore, suggested that the NaS phenomenon would be a pertinent tracer for nonlinear wave studies in the atmosphere. This is a provisional file, not the final typeset article• The solitary wave theory is proposed to be a candidate to explain the fine structure of some particular NaS events.• A solitary wave fit was made to the observations from Andes Lidar Observatory and 24/27 NaS events exhibited similar features to a soliton.• Time series of the net anomaly of the NaS revealed similar dynamical process to the solution of a generalized five-order KdV equation.